PENDAMPINGAN DALAM MENDAFTARKAN LEGALITAS UMKM DI DESA TRIDAYA SAKTI - Haekel Thadjrizky; Celsyah; Aisyah Nurul Aeni; Lala Intan Nurcahyani; Aniva Dea Imani; Cindi Eva Sundari; M. Aqil Siraj Zaini; Muhamad Ridwan (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
In order to seek acceleration and ease of businesslicensing for the business world, especially Micro, Small andMedium Enterprises (IUMK), the Indonesian government, in thiscase, made a breakthrough by launching an online integratedbusiness licensing scheme or Online Single Submission (OSS).This system greatly facilitates UMKM in managing businesslicensing because UMKM actors only need to access the OSSpage via website www.oss.go.id. to get an account. The accountis used to register by filling in the business actor's data. After thedata is completely filled in, the business actor will get an outputin the form of a Business Identification Number (NIB) and aMicro Small Business Permit (IUMK) in the form of softcopy.